Effect of partial inhibition of fatty acid oxidation by trimetazidine on whole body energy metabolism in patients with chronic heart failure. Issue 18 (23rd June 2011) - Fragasso, Gabriele; Salerno, Anna; Lattuada, Guido; Cuko, Amarild; Calori, Giliola; Scollo, Antonella; Ragogna, Francesca; Arioli, Francesco; Bassanelli, Giorgio; Spoladore, Roberto; Luzi, Livio; Margonato, Alberto; et al.
Abstract : Objective: Trimetazidine may have beneficial effects on left ventricular (LV) function in patients with systolic heart failure. The authors assessed whether long-term addition of trimetazidine to conventional treatment could improve, along with LV function, resting whole body energy metabolism in patients with chronic systolic heart failure. Design: Single blind randomised study. Setting: University Hospital. Patients: 44 patients with systolic heart failure receiving full medical treatment. Interventions: Indirect calorimetry and two-dimensional echocardiography at baseline and after 3 months. Main outcome measures: Whole body resting energy expenditure (REE), percentage of predicted REE, LV ejection fraction (EF), NYHA class, quality of life. Results: Trimetazidine increased EF compared with conventional therapy alone (from 35±8% to 42±11% vs from 35±7% to 36±6%; p=0.02, analysis of variance for repeated measures). NYHA class and quality of life also improved compared with conventional therapy (p<0.0001). REE (from 1677±264 to 1580±263 kcal/day) and percentage of predicted REE (based on the Harris–Benedict equation: from 114±10% to 108±9%) decreased in the trimetazidine group, but not in the control group (REE from 1679±304 to 1690±337 kcal/day and percentage of predicted REE from 113±12% to 115±14%). The variation was different between groups (p=0.03 and 0.023, respectively). Conclusions: In patients with systolic heart failure, improvement in functional class and LV function induced by middle-term trimetazidine therapy is paralleled by a reduction in whole body REE. The beneficial cardiac effects of trimetazidine may be also mediated by a peripheral metabolic effect.